Persepsi Remaja Awal terhadap Kekerasan Verbal di Kota Kupang - Maria Nelsanora Ismael; Diana Aipipidely; Marleny P. Panis (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine early adolescents’ perceptions of verbal violence in Kupang City. The study employed a descriptive qualitative approach involving early adolescents aged 12–15 years who had experienced verbal violence. Participants were selected using purposive sampling techniques. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that early adolescents perceive verbal violence in two categories, namely normal and abnormal behavior. Verbal violence tends to be considered normal when carried out by parents in the context of discipline, but is considered inappropriate when it involves insults, ridicule, threats, and negative labeling that hurt feelings and lower self-esteem. Forms of verbal violence experienced by adolescents include shouting, mocking, threatening, and degrading expressions originating from parents and peers. The impacts experienced include emotional distress, decreased self-confidence, social withdrawal, and feelings of insecurity. The study highlights the importance of positive communication patterns within families and schools to prevent verbal violence against adolescents.